2004
DOI: 10.1097/01.ccm.0000104944.18636.b2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of density area in dorsal lung region during prone position using transesophageal echocardiography

Abstract: It was possible to observe the change in density area during prone position using transesophageal echocardiography. The change of density area estimated with transesophageal echocardiography during prone position was useful to estimate the effectiveness of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Transthoracic lung ultrasound has several advantages over conventional radiological means for assessing lung aeration: it is reliable and accurate (17,18,23), highly reproducible (34), noninvasive, and easily repeatable at the bedside. Several studies have demonstrated that lung ultrasound is accurate for assessing positive end-expiratory pressure and prone position-induced lung recruitment (17,(35)(36)(37), lung reaeration following antimicrobial therapy in ventilator-associated and communityacquired pneumonia (18), and lung reaeration associated with resolution of various forms of pulmonary edema (38)(39)(40)(41)(42)(43)(44). Although the ultrasound detection of SBT-induced lung derecruitment does not give any indication about the cause of aeration loss, upper airway obstruction, persisting pneumonia, congestive heart failure, aspiration of secretions, cough inefficient to remove excessive bronchial secretions, and muscle weakness as observed in critically ill patients with polyneuropathy, it can be used as a predictor of extubation failure.…”
Section: Discussionmentioning
confidence: 99%
“…Transthoracic lung ultrasound has several advantages over conventional radiological means for assessing lung aeration: it is reliable and accurate (17,18,23), highly reproducible (34), noninvasive, and easily repeatable at the bedside. Several studies have demonstrated that lung ultrasound is accurate for assessing positive end-expiratory pressure and prone position-induced lung recruitment (17,(35)(36)(37), lung reaeration following antimicrobial therapy in ventilator-associated and communityacquired pneumonia (18), and lung reaeration associated with resolution of various forms of pulmonary edema (38)(39)(40)(41)(42)(43)(44). Although the ultrasound detection of SBT-induced lung derecruitment does not give any indication about the cause of aeration loss, upper airway obstruction, persisting pneumonia, congestive heart failure, aspiration of secretions, cough inefficient to remove excessive bronchial secretions, and muscle weakness as observed in critically ill patients with polyneuropathy, it can be used as a predictor of extubation failure.…”
Section: Discussionmentioning
confidence: 99%
“…Gattinoni et al described that, when body position was changed from supine to prone, there was a dramatic redistribution of lung densities from the dorsal to the ventral visualized by CT [4]. Additionally, transesophageal echocardiography (TEE) has been used to observe the change in density area while patients were in PP [12]. However, both CT and TEE are not easily accessible in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In patients on mechanical ventilation, US can be considered a reliable method to detect nonaerated lung regions [16]. Previous studies have shown the utility of US in the detection and quantification of lung recruitment via a transesophageal approach [17-19] and only recently via a transthoracic approach [20]. …”
Section: Introductionmentioning
confidence: 99%